Backing ring for vapor deposition of carbon-based brake disc and preparation method of backing ring

By using waste carbon powder and phenolic resin machined by carbon-carbon thermal field products, combined with molding process and hot pressing curing technology, low-cost and high-performance carbon-based brake disc vapor deposition pad ring is prepared, solving the problem of high cost of existing graphite pad rings and achieving compressive strength and better comprehensive performance as that of graphite pad rings.

CN119898992APending Publication Date: 2025-04-29SHAANXI MEILAND NEW MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510094991.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The graphite pad ring used in the vapor phase deposition of existing carbon-based brake discs is costly and it is difficult to meet the needs of low-cost and high-performance.

Method used

The waste carbon powder after the processing of carbon-carbon heat field products is used as raw material, and the pad ring is prepared by combining phenolic resin and molding process. The pad ring is formed by preliminary treatment of low temperature and low pressure and temperature-enhancing and pressurization to form a pad ring with high compressive strength.

Benefits of technology

The prepared pad ring has a compressive strength comparable to that of the graphite pad ring, but the cost is greatly reduced. At the same time, the comprehensive performance of the pad ring is improved by the combination of phenolic resin and carbon fiber cloth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898992A_ABST
    Figure CN119898992A_ABST
Patent Text Reader

Abstract

The invention relates to the field of carbon materials, and particularly discloses a backing ring for vapor deposition of a carbon-based brake disc and a preparation method thereof.The preparation method comprises the following steps that S1, machining residual carbon powder of a carbon-carbon thermal field product is collected as a raw material, and a carbon powder raw material is obtained after screening; s2, mixing a carbon powder raw material with phenolic resin powder to obtain a premix; s3, the premix is subjected to heat preservation treatment for 1-30 min under the conditions that the temperature is 90-110 DEG C and the pressure is 0-2 MPa, then the premix is pressurized to 3-5 MPa at the temperature of 110-130 DEG C and treated for 1-20 min, then the premix is heated to 165-180 DEG C and cured for 1-20 min, and the backing ring is obtained; the invention further discloses the backing ring prepared through the method, and the backing ring has the advantages that the backing ring which is novel, low in cost and high in performance is obtained so as to meet the requirement application of current carbon-carbon composite materials and carbon-ceramic composite materials in the vapor deposition process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of carbon materials, and more specifically, to a gasket ring for vapor deposition of a carbon-based brake disc and a preparation method thereof. Background Art

[0002] Carbon-carbon brake discs and carbon-ceramic brake discs, as carbon-based brake discs, have excellent high-temperature stability, can maintain high strength and hardness in high-temperature environments, and are not prone to thermal decay. This enables the brake system to maintain stable braking performance during high-intensity and high-frequency braking processes, thereby improving the reliability and safety of braking.

[0003] As high-performance brake materials, carbon-carbon brake discs and carbon-ceramic brake discs have broad application prospects in high-energy braking fields such as automobiles, high-speed trains, and airplanes. The vapor deposition process is one of the key technologies for preparing carbon-carbon brake discs or carbon-ceramic brake discs. It converts gaseous precursors into solid deposits at high temperatures to form one or more layers of carbon or silicon carbide materials on the brake disc substrate, thereby improving its density and performance. The gasket plays a vital role in the chemical vapor deposition densification process of carbon-carbon brake discs and carbon-ceramic brake discs.

[0004] Currently, commonly used gaskets are made of medium-coarse graphite, but the cost of graphite gaskets is relatively high. Therefore, it is necessary to develop a new, low-cost and high-performance gasket to meet the current application needs of carbon-carbon composites and carbon-ceramic composites in the vapor deposition process. Summary of the invention

[0005] In order to obtain a new, low-cost and high-performance gasket to meet the current application needs of carbon-carbon composite materials and carbon-ceramic composite materials in the vapor deposition process, the present application provides a carbon-based brake disc vapor deposition gasket and a preparation method thereof.

[0006] In a first aspect, the present application provides a method for preparing a gasket ring for vapor deposition of a carbon-based brake disc, using the following technical solution: A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc comprises the following steps: S1. Collect residual carbon powder from machining of carbon-carbon thermal field products as raw material, and obtain carbon powder raw material after sieving; S2, mixing the carbon powder raw material with the phenolic resin powder to obtain a premix; S3. The premix is ​​first heat-treated at 90-110° C. and a pressure of 0-2 MPa for 1-30 min, then pressurized to 3-5 MPa at 110-130° C. for 1-20 min, and then heated to 165-180° C. for curing for 1-20 min to obtain a gasket ring.

[0007] By adopting the above technical solution, the waste carbon powder after machining of carbon-carbon thermal field products is used as raw material in this application, and the gasket ring finally obtained by cooperating with the phenolic resin and molding process in this application has excellent compressive strength, which is equivalent to that of graphite gasket rings. Moreover, the gasket ring processing and material costs are greatly reduced by processing waste materials in this application. In addition, in this application, the carbon powder in the waste material is used as the base material, and the phenolic resin is used as the binder, and then molding is performed. During the molding process, the mixture of carbon powder and phenolic resin is subjected to pressure and temperature in the mold. The pressure helps to make the carbon powder particles in close contact, and the temperature softens the phenolic resin and causes a cross-linking reaction. These reactions enable the phenolic resin to penetrate between the carbon powder particles to form a strong chemical bond.

[0008] In the present application, the treatment is first carried out at low temperature and low pressure to allow the phenolic resin and the carbon powder to undergo preliminary physical and chemical bonding, which helps the resin to penetrate between the carbon powder particles. The temperature and pressure treatment is then carried out. The high pressure conditions help the resin to be more tightly filled between the carbon powder particles to form a denser structure, which helps the phenolic resin to be fully cross-linked and cured under high pressure. Finally, the treatment is carried out at high temperature to ensure that the phenolic resin is completely cured. Finally, when the treatment reaches the softening point of the phenolic resin in the present application, the resin begins to flow and fill the gaps between the carbon powder particles. As the temperature further increases and the pressure is applied, the phenolic resin undergoes a cross-linking reaction to form a network structure. These network structures firmly bind the carbon powder particles together to form a gasket with a certain strength and hardness.

[0009] Optionally, the phenolic resin content in the premix in step S2 is 3-20 wt %.

[0010] By adopting the above technical solution and controlling the mass ratio of phenolic resin and carbon powder, the resin can better fill the gaps between the carbon powder particles and more tightly wrap the carbon powder particles to form a stronger chemical bond with better strength, and finally the gasket performance is better.

[0011] Optionally, the particle size of the carbon powder raw material in step S1 is 20-200 mesh.

[0012] By adopting the above technical solution, since there may be a small amount of carbon fiber remaining in the carbon powder waste from the machining of carbon-carbon thermal field products, due to the difference in thermal expansion coefficients between carbon fiber and phenolic resin, when carbon fiber is added, the gasket ring will generate internal stress when the temperature changes due to the mismatch of thermal expansion coefficients, affecting the performance of the gasket ring, and the addition of carbon fiber will also increase the brittleness of the gasket ring to a certain extent, reducing the impact resistance. Therefore, in this application, the carbon powder raw material is obtained after the carbon powder added to the carbon-carbon thermal field product is sieved, and the addition of carbon fiber is removed, thereby alleviating the generation of thermal stress in the gasket ring due to brittleness and thermal expansion difference, and improving the comprehensive performance of the gasket ring.

[0013] Optionally, the heating rate in step S3 is 1-5°C / min.

[0014] By adopting the above technical scheme and controlling the heating rate, on the one hand, it is possible to prevent the rapid heating due to the difference in thermal expansion coefficients between the carbon powder and the phenolic resin from causing thermal stress and reducing the strength. On the other hand, the incomplete curing of the phenolic resin will affect its mechanical properties. Therefore, the heating rate in this application is used to prevent the excessively fast heating rate from causing thermal stress and incomplete curing from causing defects and a weak environment inside the gasket, thereby reducing its mechanical properties.

[0015] Optionally, Peek is further added to the premix in step S2, and the content of Peek in the premix is ​​1-3wt%.

[0016] By adopting the above technical solution, some Peek is added in the present application. On the one hand, its high tensile modulus and tensile strength can help improve the bearing capacity of the gasket when it is under stress and improve its strength. On the other hand, its excellent high temperature resistance can further improve the thermal stability of the gasket, so that it can maintain its shape and performance in a high temperature environment. At the same time, Peek has a lower thermal expansion coefficient, which can act as a "diluent" to reduce the thermal expansion coefficient of the overall material, thereby reducing the difference in thermal expansion coefficient of the mixed system and improving its mechanical properties.

[0017] Optionally, the preparation method further undergoes the following operations after step S3: S4, wrapping the outer peripheral surface of the gasket ring obtained after the curing treatment in step S3 with a layer of carbon fiber cloth, the carbon fiber cloth is ultrasonically impregnated in an impregnation solution containing liquid phenolic resin, nano-carbon tubes, graphite and carbon powder raw materials for 5-15 minutes, then taken out and dried, and then pressurized and cured to obtain a gasket ring.

[0018] By adopting the above technical scheme, in the present application, a layer of impregnated carbon fiber cloth is wrapped on the outer peripheral surface of the gasket ring made by molding and curing carbon powder raw material and phenolic resin. On the one hand, the carbon fiber cloth forms a reinforcement layer on the outer peripheral surface of the gasket ring, which has a significant reinforcement effect on the outer peripheral surface of the gasket ring, and the carbon fiber cloth is tightly combined with the gasket base material. The liquid phenolic resin in the impregnation liquid serves as an interface binder, and the carbon nanotube nanomaterial can significantly improve the mechanical properties and thermal stability of the material due to the size effect and surface effect. The addition of nanomaterials can fill the microscopic defects in the material and improve the density and strength of the material. At the same time, the thermal expansion coefficient of nanomaterials is usually similar to that of phenolic resin, and the thermal expansion difference of the material will not be significantly increased. Graphite, as a carbon material with a layered structure, has good thermal stability; Moreover, in the present application, a carbon fiber cloth is wrapped around the circumference of the gasket ring to form a carbon fiber composite material layer, which forms a tightly bonded interface with the gasket ring matrix through impregnation liquid and curing treatment, which can absorb and disperse the thermal stress caused by the difference in thermal expansion coefficients to a certain extent. In particular, the addition of graphite and carbon nanotubes helps to reduce the thermal stress caused by the difference in thermal expansion coefficients between phenolic resin and carbon fiber. Compared with directly adding carbon fiber to the premix and then performing molding, it greatly alleviates the reduction in mechanical properties caused by the thermal stress formed by the difference in thermal expansion between the carbon fiber and phenolic resin in the premix. Finally, the carbon fiber cloth is subjected to the above-mentioned impregnation treatment and then to a curing treatment, so that the above-mentioned nanomaterials and graphite materials are uniformly infiltrated into the fiber gaps of the carbon fiber cloth, ensuring that the carbon fiber is tightly bonded to the gasket ring matrix to form a circumferential reinforcement layer, avoiding gaps and defects at the interface, and improving the overall performance of the composite material layer gasket ring, with higher performance, performance stability and service life.

[0019] Optionally, the impregnation solution includes 8-15wt% phenolic resin, 10-15wt% carbon powder raw material, 5-8wt% carbon nanotubes, 1-3wt% graphite and the balance ethanol.

[0020] By adopting the above technical scheme, when the carbon fiber cloth is impregnated with the above impregnation liquid, substances such as carbon powder raw materials in the impregnation liquid enter into the gaps of the carbon fiber cloth, and are tightly combined with the gasket base material in the subsequent molding process. In addition, the carbon powder raw materials and carbon nanotubes can significantly improve the wear resistance of the gasket, and the addition of phenolic resin and carbon nanotubes can improve the heat resistance of the gasket, so that the gasket maintains stable performance at high temperatures and will not deform or fail. In addition, after the impregnation treatment in step S4, it is dried and then cured to remove the solvent to prevent the residual solvent from generating bubbles during the curing process or affecting the curing effect.

[0021] Optionally, the immersion temperature in the immersion liquid is 45-55°C.

[0022] Optionally, the specific parameters of pressurized curing in step S4 are: pressurizing to 1-3 MPa at 130-150° C. and curing for 10-20 min, then heating to 170-180° C. and curing at 5-8 MPa for 10-20 min.

[0023] By adopting the above technical solution, the bonding between the carbon fiber cloth and the gasket base material is better achieved under the above curing parameters, and ultimately the performance of the overall gasket is better.

[0024] In a second aspect, the present application provides a gasket ring for vapor deposition of a carbon-based brake disc, which adopts the following technical solution: a gasket ring for vapor deposition of a carbon-based brake disc, which is prepared by the preparation method.

[0025] By adopting the above technical solution, the gasket ring prepared by the preparation method in this application has excellent mechanical properties such as compressive strength, and it is made by processing waste materials of carbon-carbon thermal field products, which greatly reduces costs.

[0026] In summary, this application has the following beneficial effects: 1. In this application, waste carbon powder after machining of carbon-carbon thermal field products is used as raw material. The gasket ring finally obtained by combining with phenolic resin and molding process in this application has excellent compressive strength, which is equivalent to that of graphite gasket ring. Moreover, in this application, it is processed from waste materials, which greatly reduces the processing and material costs of the gasket ring. In addition, in this application, carbon powder in waste materials is used as the base material, phenolic resin is used as the binder, and then molding is performed. During the molding process, the mixture of carbon powder and phenolic resin is subjected to pressure and temperature in the mold. The pressure helps to make the carbon powder particles in close contact, while the temperature softens the phenolic resin and causes a cross-linking reaction. These reactions enable the phenolic resin to penetrate between the carbon powder particles to form a strong chemical bond. 2. In the present application, the treatment is first carried out at low temperature and low pressure to allow the phenolic resin and the carbon powder to undergo preliminary physical and chemical bonding, which helps the resin to penetrate between the carbon powder particles. The treatment is then carried out under elevated temperature and pressurized conditions. The high pressure conditions help the resin to be more tightly filled between the carbon powder particles to form a denser structure, which helps the phenolic resin to be fully cross-linked and cured under high pressure. Finally, the treatment is carried out at high temperature to ensure that the phenolic resin is completely cured. When the treatment reaches the softening point of the phenolic resin in the present application, the resin begins to flow and fill the gaps between the carbon powder particles. As the temperature further increases and the pressure is applied, the phenolic resin undergoes a cross-linking reaction to form a network structure. These network structures firmly bind the carbon powder particles together to form a gasket with a certain strength and hardness. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a photograph of the gasket ring prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0028] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0029] The carbon-carbon thermal field products in this application specifically refer to thermal field products such as carbon-carbon guide tubes, carbon-carbon support rods, and carbon-carbon insulation tubes.

[0030] The carbon-based brake disc in the present application is a carbon / carbon composite brake disc or a carbon-ceramic brake disc. The gasket ring prepared in the present application is used for sealing and spacing the above-mentioned carbon-carbon brake disc or carbon-ceramic brake disc preform during the vapor deposition densification process. When used, the carbon-based brake disc needs to be pressed against the edge of the gasket ring, so the prepared gasket ring has certain requirements for compressive strength.

[0031] In the following examples, the phenolic resin powder is selected from the water-soluble / alcohol-soluble phenolic resin powder of Wuhan Xinzhongxin Chemical Technology Co., Ltd.; In the following examples, the phenolic resin liquid is selected from the alcohol-soluble phenolic resin liquid with a brand number of 6560 produced by Jining Fangyu Chemical Co., Ltd.

[0032] Example 1 A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc comprises the following steps: S1. Collect residual carbon powder from machining of carbon-carbon thermal field products as raw material, and obtain carbon powder raw material after sieving. The particle size of the carbon powder raw material is 20-200 meshes; S2, mixing the carbon powder raw material with the phenolic resin powder to obtain a premix, wherein the phenolic resin content in the premix is ​​10wt%; S3, preheating the gasket ring mold, the preheating temperature is 100 ° C, the premixed material mixed in step S2 is sprinkled in the mold for pressurization, and heat preservation treatment is carried out at 100 ° C and pressure of 1 MPa for 15 minutes, and then the temperature is increased to 120 ° C at a heating rate of 3 ° C / min, and the pressure is increased to 4 MPa for 10 minutes at this temperature and pressure, and then the temperature is increased to 170 ° C at a heating rate of 3 ° C / min, and the gasket ring is cured at this temperature for 10 minutes to obtain Figure 1 shown.

[0033] Example 2 A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc comprises the following steps: S1. Collect residual carbon powder from machining of carbon-carbon thermal field products as raw material, and obtain carbon powder raw material after sieving. The particle size of the carbon powder raw material is 20-200 meshes; S2, mixing the carbon powder raw material with the phenolic resin powder to obtain a premix, wherein the phenolic resin content in the premix is ​​3wt%; S3. Preheat the gasket ring mold to 90°C, sprinkle the premix mixed in step S2 into the mold for pressurization, and keep it warm at 90°C and normal pressure for 30 minutes, then heat it to 130°C at a heating rate of 5°C / min, and pressurize it to 5MPa for 1 minute at this temperature and pressure, then heat it to 165°C at a heating rate of 1°C / min, and cure it at this temperature for 20 minutes to obtain the gasket ring.

[0034] Example 3 A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc comprises the following steps: S1. Collect residual carbon powder from machining of carbon-carbon thermal field products as raw material, and obtain carbon powder raw material after sieving. The particle size of the carbon powder raw material is 20-200 meshes; S2, mixing the carbon powder raw material with the phenolic resin powder to obtain a premix, wherein the phenolic resin content in the premix is ​​20wt%; S3. Preheat the gasket ring mold at a preheating temperature of 110°C, sprinkle the premix mixed in step S2 into the mold for pressurization, and keep it warm at 110°C and a pressure of 2MPa for 1 min, then heat it to 110°C at a heating rate of 1°C / min, and pressurize it to 3MPa for 20 min at this temperature and pressure, then heat it to 180°C at a heating rate of 5°C / min, and cure it at this temperature for 1 min to obtain the gasket ring.

[0035] Example 4 A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc is carried out according to the method in Example 1, except that Peek is further added to the premix in step S2, and the Peek content in the premix is ​​1wt%.

[0036] Example 5 A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc is carried out according to the method in Example 1, except that Peek is further added to the premix in step S2, and the Peek content in the premix is ​​3wt%.

[0037] Example 6 A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc is carried out according to the method in Example 1, except that the gasket ring in the present application is made by molding and curing the gasket ring substrate and the outer peripheral surface of the gasket ring substrate wrapped with a layer of pretreated carbon fiber cloth in a mold, wherein the gasket ring substrate is processed according to the method in Example 1, the gasket ring substrate is obtained after molding and curing in step S3, and then the following step S4 is also performed: S4. Wrap a layer of pretreated carbon fiber cloth on the outer peripheral surface of the gasket ring obtained after the curing treatment in step S3. More specifically, the pretreated carbon fiber cloth is obtained by ultrasonically impregnating the carbon fiber cloth in an impregnation solution containing liquid phenolic resin, carbon nanotubes, graphite and carbon powder raw materials for 10 minutes and then taking it out and drying it. The impregnation temperature is 50°C, and the impregnation solution is ultrasonically mixed with 12wt% phenolic resin, 12wt% carbon powder raw materials, 6wt% carbon nanotubes and 2wt% graphite and the remainder ethanol. After the impregnation is completed, the gasket ring wrapped with the carbon fiber cloth is placed in a mold and pressurized to 2MPa at 140°C for curing for 15min, then heated to 175°C and cured at 6MPa for 15min. After the curing is completed, the edges are trimmed and the surface is polished to obtain the gasket ring.

[0038] In the present application, in step S3, the mold is adjusted to reserve space for the carbon fiber cloth in step S4, and the thickness of the gasket base material in the gasket is finally 4 / 5 of the thickness of the gasket.

[0039] Example 7 A method for preparing a gasket for vapor deposition of a carbon-based brake disc is carried out according to the method in Example 6, except that, in step S4, the outer peripheral surface of the gasket obtained after the curing treatment in step S3 is wrapped with a layer of pretreated carbon fiber cloth. More specifically, the pretreated carbon fiber cloth is obtained by ultrasonically impregnating the carbon fiber cloth in an impregnation solution containing liquid phenolic resin, carbon nanotubes, graphite and carbon powder raw materials for 5 minutes and then taking it out and drying it. The impregnation temperature is 45°C, and the impregnation solution is obtained by ultrasonically mixing 8wt% of phenolic resin, 10wt% of carbon powder raw materials, 5wt% of carbon nanotubes and 1wt% of graphite and the remainder of ethanol. After the impregnation is completed, the gasket wrapped with the carbon fiber cloth is placed in a mold and pressurized to 1MPa at 130°C for curing for 20 minutes, then heated to 170°C and cured at 5MPa for 20 minutes. After the curing is completed, the edges are trimmed and the surface is polished to obtain the gasket.

[0040] Example 8 A method for preparing a gasket for vapor deposition of a carbon-based brake disc is carried out according to the method in Example 6, except that, in step S4, the outer peripheral surface of the gasket obtained after the curing treatment in step S3 is wrapped with a layer of pretreated carbon fiber cloth. More specifically, the pretreated carbon fiber cloth is obtained by ultrasonically impregnating the carbon fiber cloth in an impregnation solution containing liquid phenolic resin, carbon nanotubes, graphite and carbon powder raw materials for 15 minutes and then taking it out and drying it. The impregnation temperature is 55°C, and the impregnation solution is obtained by ultrasonically mixing 15wt% of phenolic resin, 15wt% of carbon powder raw materials, 8wt% of carbon nanotubes and 3wt% of graphite and the remainder of ethanol. After the impregnation is completed, the gasket wrapped with the carbon fiber cloth is placed in a mold and pressurized to 3MPa at 150°C for curing for 10 minutes, then heated to 180°C and cured at 8MPa for 10 minutes. After the curing is completed, the edges are trimmed and the surface is polished to obtain the gasket.

[0041] Example 9 A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc is carried out according to the method in Example 6, except that an equal amount of carbon nanotubes in the impregnation solution in step S4 is replaced by a carbon powder raw material.

[0042] Example 10 A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc is carried out according to the method in Example 6, except that an equal amount of the carbon powder raw material in the impregnation liquid in step S4 is replaced by carbon nanotubes.

[0043] Comparative Example 1 A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc is carried out according to the method in Example 1, except that the curing parameters in step S3 are: directly hot pressing at 180° C. and 18 MPa pressure for 5 minutes.

[0044] Comparative Example 2 A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc is carried out according to the method in Example 1, except that a constant pressure of 5 MPa is maintained during the treatment process in step S3.

[0045] Comparative Example 3 A method for preparing a gasket ring for vapor deposition of a carbon-based brake disc is carried out according to the method in Example 1, except that the treatment in step S3 is maintained at a constant temperature of 170°C.

[0046] Comparative Example 4 A method for preparing a gasket for carbon-based brake disc vapor deposition is carried out according to the method in Example 1, except that carbon fiber is also added to the premix in step S2, and the carbon fiber content is 5wt%.

[0047] Performance Testing The gaskets prepared in the examples and comparative examples of the present application were tested for compressive performance. The specific operation was: a heavy object was pressed on the prepared gasket (with the same size, shape and specifications), and the weight of the heavy object when the gasket was pressed to the point of cracks, ruptures and other damage was counted to consider its compressive performance. The statistical results are shown in Table 1 below.

[0048] Table 1: When the gasket is used, the carbon-carbon brake disc or carbon-ceramic brake disc is pressed on the gasket. Therefore, the higher the compression resistance of the gasket, the greater the weight of the brake disc it can bear, and it can be applied to more sizes of brake discs, and its service life is longer. Referring to the test results in the embodiments of the present application, the gasket prepared in the present application can bear a brake disc weight of 150kg. Combined with the test results of Example 1 and Example 4-5, when Peek is added to the premix, Peek provides a certain buffer, improves its compression resistance, and its difference in thermal expansion coefficient for the mixed system is reduced, and its compression resistance is increased; combined with the test results of Examples 6-8, when the gasket structure includes a gasket substrate molded with carbon powder and phenolic resin and an outer cladding structure formed by carbon fiber cloth, the carbon fiber cloth circumferential surface wrapping significantly improves the mechanical properties of the gasket circumferential surface, and its compression resistance is significantly improved. Combined with the test results of Examples 9-10, when no nano carbon tubes or carbon powder raw materials are added during the impregnation of the carbon fiber cloth, its compressive strength is reduced.

[0049] Combined with the test results of Example 1 and Comparative Examples 1-3, it can be seen that when the gasket ring in the present application is prepared with carbon powder and phenolic resin as the base material, when it adopts a single constant temperature and constant pressure treatment, its compressive performance is significantly reduced, which may be due to the influence of internal thermal stress or curing rate. Combined with the test results of Comparative Example 4, when carbon fiber, carbon powder and phenolic resin powder are added in a mixed form, its compressive performance is significantly reduced due to differences in thermal expansion coefficients and other reasons. In the embodiment of the present application, when it is wrapped with carbon fiber cloth around the periphery of the carbon powder gasket base material and carbon powder, graphite and carbon nanotubes are also added, its mechanical properties are better.

[0050] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a gasket ring for carbon-based brake disc vapor deposition, characterized in that The following steps are involved: S1. Collect residual carbon powder from machining of carbon-carbon thermal field products as raw material, and obtain carbon powder raw material after sieving; S2, mixing the carbon powder raw material with the phenolic resin powder to obtain a premix; S3. The premix is ​​first heat-treated at 90-110° C. and a pressure of 0-2 MPa for 1-30 min, then pressurized to 3-5 MPa at 110-130° C. for 1-20 min, and then heated to 165-180° C. for curing for 1-20 min to obtain a gasket ring.

2. The method for preparing a carbon-based brake disc gasket for vapor deposition according to claim 1, characterized in that: The content of phenolic resin in the premix in step S2 is 3-20wt%.

3. The method for preparing a carbon-based brake disc gasket for vapor deposition according to claim 1, characterized in that: The particle size of the carbon powder raw material in step S1 is 20-200 mesh.

4. The method for preparing a carbon-based brake disc gasket for vapor deposition according to claim 1, characterized in that: The heating rate in step S3 is 1-5°C / min.

5. The method for preparing a carbon-based brake disc gasket for vapor deposition according to claim 1, characterized in that: Peek is also added to the premix in step S2, and the content of Peek in the premix is ​​1-3wt%.

6. The method for preparing a carbon-based brake disc gasket for vapor deposition according to claim 1, characterized in that: The preparation method further undergoes the following operations after step S3: S4, wrapping the outer peripheral surface of the gasket ring obtained after the curing treatment in step S3 with a layer of carbon fiber cloth, the carbon fiber cloth is ultrasonically impregnated in an impregnation solution containing liquid phenolic resin, nano-carbon tubes, graphite and carbon powder raw materials for 5-15 minutes, then taken out and dried, and then pressurized and cured to obtain a gasket ring.

7. The method for preparing a carbon-based brake disc gasket for vapor deposition according to claim 6, characterized in that: The impregnation liquid includes 8-15wt% of phenolic resin, 10-15wt% of carbon powder raw material, 5-8wt% of carbon nanotubes, 1-3wt% of graphite and the balance of ethanol.

8. The method for preparing a carbon-based brake disc gasket for vapor deposition according to claim 6, characterized in that: The immersion temperature in the immersion liquid is 45-55°C.

9. The method for preparing a carbon-based brake disc gasket for vapor deposition according to claim 6, characterized in that: The specific parameters of pressurized curing in step S4 are: pressurized to 1-3 MPa at 130-150° C. and cured for 10-20 min, then heated to 170-180° C. and cured at 5-8 MPa for 10-20 min.

10. A carbon-based brake disc gasket for vapor deposition prepared by the preparation method according to any one of claims 1 to 9.